Therapeutic benefits of Carica papaya: A review on its pharmacological activities and characterization of papain - Benjamin Ayodipupo Babalola; Amos Ifeolu Akinwande; Adebisi A. Otunba; Gboyega Ebenezer Adebami; Oluwabukunmi Babalola; Chekwube Nwufo (Arabian Journal of Chemistry, 2024)
Carica papaya, commonly referred to as papaya, is a member of the Caricaceae family, boasting a diverse array of compounds and biomolecules, notably papain, with significant industrial and medicinal value. This comprehensive review meticulously examines the properties, extraction techniques, and pharmacological importance of papain, coupled with an exploration of the pharmacological activities inherent in C. papaya. Extensive research data from reputable sources such as Google Scholar, PubMed, Scopus, and Web of Science were scrutinized to collate pertinent information on the plant and its enzyme. Within C. papaya, a spectrum of bioactive compounds were identified, encompassing alkaloids, tannins, phenolics, flavonoids, saponins, terpenoids, sugars, glycosides, amino acids, steroids, and the pivotal enzyme papain. Papain extraction methods and their activity modulation in response to pH, temperature, and other physicochemical parameters were examined in detail. This review provides a nuanced analysis of papain, addressing both its pharmacological implications and potential side effects. Its far-reaching applications in the medical, industrial, and pharmaceutical sectors were meticulously discussed, unveiling its market potential. Furthermore, C. papaya emerged as a reservoir of pharmacological activities, exhibiting antioxidant properties, anti-cancer potential, wound healing capabilities, digestive disorder management, and anxiolytic effects. The research underscores the promising potential of C. papaya and papain for diverse biological applications, prompting a call for further studies to unlock their therapeutic benefits, particularly in the realm of public health. Looking ahead, continued advancements in drug development hold the key to unraveling the intricate bioactive components of papaya and its papain cysteine proteases. These insights are poised to catalyze their development and application, promising substantial contributions to the betterment of humanity.